The space-bandwidth product in the joint transform correlator optical encryption setup - Cuadrado Laborde, Christian Ariel (2011)
In this work we study the joint transform correlator (JTC) optical encryption setup through the Wigner function. We found analytical expressions for the spatial and spatial frequency extent of the encrypted signal. Since the JTC is inherently an asymmetrical optical system, different expressions were found for each spatial axis and for their associated spatial frequency axes. We also compare these results with the dual random phase encoding technique. Finally, we found an analytical expression for the minimum separation between channels that avoids crosstalk in a wavelength multiplexing JTC architecture.